2014
DOI: 10.1186/s13000-014-0169-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary spleen extranodal NK/T cell lymphoma, nasal type, with bone marrow involvement and CD30 positive expression: a case report and literature review

Abstract: AimsPrimay spleen NK/T cell lymphoma is very rare. We report a case of 39-years-old male of primary splenic NK/T cell lymphoma with bone marrow involvement and CD30 positive expression.Case descriptionThe patient had high fever for 2 months, and CT scan revealed a diffuse splenomegaly without hepatomegaly. The diagnosis was established by splenectomy specimen and bone marrow biopsy. Normal spleen structure was destroyed by the diffusely infiltrated neoplastic cells, and one of the splenic hilar lymph nodes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…This expression rate is higher than the 30% in the WHO book of ENKTL . In de novo ENKTL, large cell morphology usually correlates with CD30 expression; and in some studies, a poorer prognosis . In this current study, the lymphoma cells of effusion ENKTL are usually large and anaplastic, which is distinct from de novo ENKTL.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…This expression rate is higher than the 30% in the WHO book of ENKTL . In de novo ENKTL, large cell morphology usually correlates with CD30 expression; and in some studies, a poorer prognosis . In this current study, the lymphoma cells of effusion ENKTL are usually large and anaplastic, which is distinct from de novo ENKTL.…”
Section: Discussionmentioning
confidence: 45%
“…10 Radiologic studies showed no evidence of lymphadenop- In de novo ENKTL, large cell morphology usually correlates with CD30 expression; and in some studies, a poorer prognosis. [35][36][37] In this current study, the lymphoma cells of effusion ENKTL are usually large and anaplastic, which is distinct from de novo ENKTL. We recommend that CD30 immunostaining be performed for all effusion ENKTL cases; and target therapy with brentuximab vedotin, an anti-CD30 antibody-drug conjugate, might be considered a therapeutic option for those with CD30-expressing tumors.…”
Section: Discussionmentioning
confidence: 79%
“…Pure extranodal presentation are infrequent (9% of cases). Follicular lymphomas that compromise the spleen can exhibit one of two histologic patterns 9,10,12 .…”
Section: Follicular Lymphomamentioning
confidence: 99%
“…As ENKTCL can progress to systemic disease and involve bone marrow, it might have considerable morphological and immunophenotypic similarities to ANKCL . It has been debated whether ANKCL is a real entity or simply represents a leukaemic phase of ENKTCL …”
Section: Introductionmentioning
confidence: 99%
“…1 As ENKTCL can progress to systemic disease and involve bone marrow, [2][3][4][5] it might have considerable morphological and immunophenotypic similarities to ANKCL. 11,12 It has been debated whether ANKCL is a real entity or simply represents a leukaemic phase of ENKTCL. 13,14 In order to clarify this, we studied cases of bone marrow NK/T-cell neoplasms by classifying them into groups without extramedullary tumour and with additional extramedullary tumour(s), and compared their clinicopathological features.…”
Section: Introductionmentioning
confidence: 99%